Efficacy of the Recombinant Tuberculosis Allergen for Early Identification of Latent Tuberculosis in Children and Adolescents in General Healthcare Settings - V. A. Aksenova; L. A. Baryshnikova ("Paediatrician" Publishers LLC, 2015)
Background: In Russia there are a lot of children with tuberculosis in an involution phase that is caused by poor quality of the tuberculinodiagnosis. Currently, the new intradermal test with the recombinant tuberculosis allergen (RTA) is becoming more widespread in practice of TB service specialists. Objective: To study the efficacy of the RTA in early identification of latent tuberculosis signs in children and adolescents. Methods: We conducted a multicenter retrospective study, during which we studied the results of 4 stages of the RTA application in 2008-2014. Stage 1 involved the medication use in tuberculosis dispensary settings. Following stages included TB screening in general healthcare settings. Patients were children with acute and chronic non-specific diseases as well as healthy pupils. The 4th study stage included the epidemiologic analysis of recombinant tuberculosis allergen application results all over the Russian Federation. Results: During the study a phthisiologist identified 763 patients in categories of children and adolescents with the highest disease risk (39.5%); TB identification in 176 patients of a general hospital made 2.3%; among 1238 pupils - 0.6%. In accordance with the results of RTA application in children and adolescents 79 RF entities comprise the methods of the child population screening for tuberculosis, according to which all children after primary BCG-M vaccination should undergo immunodiagnostic work-up with tuberculin application annually. Since 8 years of age all children and adolescents undergo the annual immunodiagnostic work-up with RTA application. Conclusion: RTA application in general healthcare settings enables identification of the top risk groups for acquiring tuberculosis infections and patients with early disease stages. The method of the tuberculosis detection and monitoring of risk groups was suggested (Order of the Ministry of Health of the Russian Federation No 855, 2009; No 951, 2014).